Create Brand Loyalty of IndonesÄ±an Facebook User Through Brand Engagement: UtÄ±lÄ±zatÄ±on the Role of SocÄ±al MedÄ±a MarketÄ±ng Elements - Wulandari, Astri; Suryawardani, Bethani; Marcelino, Dandy (Department of Management, Faculty of Economics and Business, Brawijaya University, 2022)
There has been a noticeable increase in businesses reaching out to a wider range of potential customers using the internet and social media to market and present their goods. Social media marketing is thought to improve brand loyalty and engagement by utilizing social media aspects such as entertaining, interactive, trend of customization/personalization, and WOM. One of the most prominent social media networks is Facebook, and it is superior to other social media platforms in Indonesia since it has the most users. There has been no study to date that investigates how Facebook as social media platform is seen a brand that offers marketing capabilities and services. This study employed quantitative research methodologies, namely causal analysis utilizing Structural Equation Modeling (SEM) techniques and the SMART PLS 3.2.9 software. This study's sample consists of Facebook or social media users in Indonesia who have viewed marketing or promotional content on their social media. The researcher's sample approach of choice is incidental sampling, with a total of 400 respondents. This study in accordance with the study's goals, may demonstrate that Facebook's social media marketing activities effect customer engagement with a brand and customer loyalty to a brand. Facebook's marketing operations in social media may promote brand engagement by users of these social media, whereby consumer engagement also mediates the link between social media marketing and brand loyalty.